DOES BASELINE SUB-FOVEAL CHORIODAL THICKNESS DETERMINES TREATMENT RESPONSE TO INTRAVITREAL AFLIBERCEPT IN DIABETIC MACULAR EDEMA? - Ranjan, Somesh; Nehra, Harshraj; Sharma, Vinod; Goel, Kashish; Kumari, Madhu; Agarwal, Sarita; Sharma, Neharika; Mehta, Bhavya; Sharma, Ram Lal; Bhargava, Rahul (International Journal of Retina, 2024)
Introduction: To determine the predictive value of baseline SFCT for response to treatment with serial intravitreal aflibercept injections for diabetic macular edema (DME). Methods: A prospective multi-center study was done. Eyes with DME (n=95) were treated with intravitreal aflibercept injections q4week for first 5 doses, followed by 2mgq8week, respectively. SFCT and central macular thickness (CMT) were measured with serial enhanced depth imaging optical coherence tomography scans done at baseline and after the last injection. A functional responder was one with >5 ETDRS letter gain in vision. An anatomical responder was one with SFCT reduction>25u. Results: At 6 months, after the last IV injection of aflibercept, the mean SFCT decreased significantly (319±47 at baseline, 250±36 at 6 months, P<0.001). A significantly higher baseline SFCT was seen in functional responders as compared to non-responders (329±50 versus 303±36u, independent t-test, P=0.002). Likewise, anatomical responders has a significantly higher baseline SFCT as compared to non-responders (327±51 versus 305±33, P=0.002). Multiple logistic regression (after adjusting for confounders like age, gender, duration of diabetes, and glycemic control, respectively) revealed that higher SFCT had increased odds of having a better functional (odds ratio=1.40, P=0.050) and anatomical outcome (odds ratio=1.23, P=0.001), respectively. The mean vision gain in functional responders and non-responders was 11and 5 ETDRS letters, respectively (P<0.001). The mean vision gain in anatomic responders and non-responders was 10 and 6 ETDRS letters, respectively (P<0.001). Conclusion: SFCT at baseline predicts response to intravitreal aflibercept therapy in DME patients after adjusting for confounders. Eyes with a thicker baseline sub-foveal choroidal thickness had better anatomic and functional response at 9 months.